2002
DOI: 10.1042/bj20011804
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine phosphorylation and dissociation of occludin–ZO-1 and E-cadherin–β-catenin complexes from the cytoskeleton by oxidative stress

Abstract: The oxidative-stress-induced alteration in paracellular junctional complexes was analysed in Caco-2 cell monolayer. Oxidative stress induced a rapid increase in tyrosine phosphorylation of occludin, zonula occludens (ZO)-1, E-cadherin and beta-catenin. An oxidative-stress-induced decrease in transepithelial electrical resistance was associated with a redistribution of occludin-ZO-1 and E-cadherin-beta-catenin complexes from the intercellular junctions. Genistein, a tyrosine kinase inhibitor, prevented the oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
379
0
8

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(406 citation statements)
references
References 35 publications
19
379
0
8
Order By: Relevance
“…[49][50][51] For both occludin and ZO-1, phosphorylation levels help regulate barrier permeability, [52][53][54] and increased paracellular permeability associated with the tyrosine phosphorylation, and dissociation of occludin and ZO-1 from the cytoskeleton can be caused by oxidative stress. 55 Furthermore, vascular endothelial growth factor (VEGF) can increase intercellular permeability by enhancing ZO-1 and occludin phosphorylation, causing displacement and the reduction of ZO-1 expression, 56,57 corroborating the role of a tyrosine kinasedependent mechanism for the association of the junctional complex to cytoskeleton. Accordingly, in the brain of mdx mice, some vascular permeability is recognizable due to alteration of TJs, such as the detachment of their external leaflet membrane, altered expression of claudin-1 and ZO-1, and increased phosphorylation of ZO-1.…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51] For both occludin and ZO-1, phosphorylation levels help regulate barrier permeability, [52][53][54] and increased paracellular permeability associated with the tyrosine phosphorylation, and dissociation of occludin and ZO-1 from the cytoskeleton can be caused by oxidative stress. 55 Furthermore, vascular endothelial growth factor (VEGF) can increase intercellular permeability by enhancing ZO-1 and occludin phosphorylation, causing displacement and the reduction of ZO-1 expression, 56,57 corroborating the role of a tyrosine kinasedependent mechanism for the association of the junctional complex to cytoskeleton. Accordingly, in the brain of mdx mice, some vascular permeability is recognizable due to alteration of TJs, such as the detachment of their external leaflet membrane, altered expression of claudin-1 and ZO-1, and increased phosphorylation of ZO-1.…”
Section: Discussionmentioning
confidence: 99%
“…ROS-induced disruption of TJ proteins by reducing the ZO-1 and occludin complex in Caco-2 cell monolayers has been reported [66]. Meanwhile, ROS can induce lipid and protein oxidative damage to destroy the integrity of epithelial cells in the intestine of Jian carp [7].…”
Section: Phe Regulated Nf-kb P65 I-kba and Tor Gene Expressions In Tmentioning
confidence: 95%
“…Previous studies have indicated that decreased expression of claudin c [68], claudin 3 [69], claudin 15 [70], occludin and ZO-1 [66] impaired the barrier function. The data presented herein showed that deficiency or excess of Phe downregulated claudin c, claudin 3 and claudin 15, occludin and ZO-1 gene expression, however, those were up-regulated by optimal Phe supplementation in all intestinal segments.…”
Section: Phe Regulated Tj Protein Transcript Abundance In the Intestimentioning
confidence: 95%
“…As shown by Hsia et al [12], a probable mechanism by which cSrc promotes invasive behavior is through formation of a transient complex with focal adhesion kinase (FAK), another protein tyrosine kinase [12]. Some evidence suggests that TJ protein phosphorylation plays an important role in the regulation of cell-cell adhesion [13,14]. It is worth noting that occludin and CRB3, intercellular binding proteins, have been used as epithelial and polarity markers in EMT studies [15,16].…”
Section: Introductionmentioning
confidence: 99%